Safeguarding Its Way to Security or Not – Should Fintech Become a Bank(Tech)? - Pawlak, Kamila (Journal of Finance and Financial Law, 2023)
The purpose of the article. This article explores the trend of fintech firms obtaining banking licenses, challenging their traditional advantage of not being banking institutions. It investigates two hypotheses: H1 – Banking licenses bring more opportunities than threats for fintech companies; H2 – Obtaining licenses positively impacts their profitability. Methodology. The study utilizes the literature review and applies Porter’s Five Forces methodology to assess the strategic implications of banking licenses for fintech firms. Financial analysis is conducted on three selected companies based on market capitalization, banking license timeline, and geographical diversification. Profitability ratios (ROE and ROA) are analyzed before and after obtaining the license. Results of the research. Fintech firms with banking licenses experience more opportunities than threats, as confirmed by Porter’s analysis. However, only one out of three analysed companies immediately improved profitability ratios after obtaining the license. In conclusion, obtaining banking licenses opens growth opportunities for fintech firms, but immediate profitability improvements are not guaranteed. Additional requirements and challenges arise during the transition to a banking area. The study acknowledges limitations and suggests further research to confirm and expand these findings in the evolving fintech landscape.